The Comparative Statics of Effective Demand. Issue 3 (3rd July 2017) - Hartwig, Jochen
ABSTRACT: Keynes introduces the term 'effective demand' in Chapter 3 of the General Theory as designating the point of intersection of two functions: the 'aggregate demand function' ( D ) and the 'aggregate supply function' ( Z ). For the first time in the literature, I here use specific functional forms for the D and Z functions and run numerical simulations which allow study of the comparative statics of the model in the face of various 'shocks'. The demonstration of how the D / Z model actually works will hopefully prove useful for future students of the economics of Keynes.